Pengaruh Model Pembelajaran Cooverative Learning Tipe Jigsaw Terhadap Keterampilan Dribbling Bola Basket Pada Siswa Kelas 11 SMA Negeri 1 Rengasdengklok - abdullah waffa; Muhammad Mury Syafei; Bambang Ismaya (Universitas Singaperbangsa, 2020)
The purpose of making this thesis is to find out, analyze, and identify the significant effect of the jigsaw learning model on the baskt dribbling skills at State High School 1 Rengasdengklok. There are three stages in this study, namely: pretest, treatment, and posttest. Pretest is done in both classes to find out the initial ability of basketball skills before getting treatment After being given treatment, the researchers then conducted a post-test in both classes to find out whether there was an effect of the jigsaw learning model in the experimental class. The results showed that the jigsaw learning model had a greater influence on the dribbling skills of Class XI of SMA Negeri 1 Rengasdengklok with a T-count result of 0.133 and compared to a T-table of 0.148 with a significance (<0.05) of 0.00